Distribution of black carbon and PAHs in sediments of Peninsular Malaysia - Vaezzadeh, Vahab (Pergamon-Elsevier Science Ltd, 2021)
Concentrations, sources and interactions between black carbon (BC) and polycyclic aromatic hydrocarbons (PAHs) were investigated in 42 sediment samples collected from riverine, coastal and shelf areas in Peninsular Malaysia. The concentrations of BC measured by benzene polycarboxylic acid (BPCA) method and PAHs showed broad spatial variations between the relatively pristine environment of the East coast and developed environment of the West and South coast ranging from 0.02 to 0.36% dw and 57.7 ng g-1 dw to 19,300 ng g-1 dw, respectively. Among diagnostic ratios of PAHs, the ratios of Ant/(Ant+Phe) and LMW/HMW drew the clearest distinctions between the East coast versus the West and South coast sediments indicating the predominance of petrogenic sources in the former versus pyrogenic sources in the latter. PAHs significantly correlated with BC and total organic carbon (TOC) in the sediments (p < 0.05) having similar correlation coefficients. BC accounted for 6.06 to 30.6% of TOC in sediments.